MENINGKATKAN KEOTENTIKAN KURIKULUM SEKOLAH ISLAM: KETERLIBATAN GURU, PRAKTIK SUPERVISI, DAN PENDAMPINGAN PARTISIPATIF - Ahmad Musaddad (Hijri, 2025)
This study examines how Islamic madrasah curricula are often administratively replicated without embedding Islamic values or local wisdom. Using an explanatory sequential mixed-methods design, we surveyed 64 teachers and curriculum coordinators, then conducted 12 in-depth interviews. Quantitative analyses (descriptive statistics, Pearson correlation, simple regression) revealed that 78% of documents received only superficial identity changes and only 27% of teachers participated actively. Teacher engagement correlated strongly with document originality (r = 0.62; p < 0.01), while supervisory effectiveness explained 28% of quality variation. Qualitative themes highlight teachers' technical unpreparedness, viewing curriculum as an administrative burden, and a need for on-site case-based coaching. We propose a participatory mentoring model combining on-site training and document review to boost teachers' technical capacity and foster authentic, reflective, context-relevant curricula. Recommendations focus on sustained supervisory policy and co-design of curricula by teachers and supervisors.